Megakaryocyte NLRP3 hyperactivation induces mild anemia and potentiates inflammatory response in mice - Bourne, Joshua H.; Campos, Joana; Hopkin, Sophie J.; Whitworth, Katharine; Palis, James; Senis, Yotis A.; Rayes, Julie; Iqbal, Asif J.; Brill, Alexander (Frontiers in Immunology, 2023)
Background. The NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome has been described in both immune cells and platelets but its role in the megakaryocyte (MK) lineage remains elusive. Objective. To explore the role of NLRP3 inflammasome in megakaryocytes and platelets. Methods. We generated Nlrp3A350V/+/Gp1ba-CreKI/+ mice carrying a mutation genetically similar to the one observed in human Muckle-Wells syndrome, which leads to hyperactivity of NLRP3 specifically in MK and platelets. Results. Platelets from the mutant mice expressed elevated levels of both precursor and active form of caspase-1 suggesting hyperactivity of NLRP3 inflammasome. Nlrp3A350V/+/Gp1ba-CreKI/+ mice developed normally and had normal platelet counts. Expression of major platelet receptors, platelet aggregation, platelet deposition on collagen under shear, and deep vein thrombosis were unchanged. Nlrp3A350V/+/Gp1ba-CreKI/+ mice had mild anemia, reduced Ter119+ cells in the bone marrow, and splenomegaly. A mild increase in MK TGF- might be involved in the anemic phenotype. Intraperitoneal injection of zymosan in Nlrp3A350V/+/Gp1ba-CreKI/+ mice induced increased neutrophil egression and elevated levels of a set of proinflammatory cytokines, IL-10 and G-CSF in the peritoneal fluid as compared with control animals. Conclusion. MK/platelet NLRP3 inflammasome promotes the acute inflammatory response and its hyperactivation in mice leads to mild anemia and increased extramedullary erythropoiesis.